Can country risks predict Islamic stock index? Evidence from Indonesia. Issue 7 (4th August 2021) - Masrizal,; Sukmana, Raditya; Al Mustofa, Muhammad Ubaidillah; Herianingrum, Sri
Abstract : Purpose: This study aims to examine the relationship between the Indonesian Islamic capital market, the country's risk and macroeconomic factors. Design/methodology/approach: This study uses the Johansen cointegration test and the vector error correction model (VECM) on monthly data from January 2003 to March 2016 to examine the variables that influenced the Islamic capital market proxied by the Jakarta Islamic Index (JII). Findings: The findings indicate the existence of short-term and long-term cointegrations between country risk (political, economic and financial risks), macroeconomic variables (industrial production index, inflation and oil price) and JII. In the long run, financial risk positively affects the JII, whereas economic risks and inflation are negatively related. In the short run, only inflation affect negatively the JII. Practical implications: The study emphasizes the critical role of financial risk in affecting the Islamic capital market. Investors negatively respond to higher financial risk and react positively to more increased economic threats. The variable of financial risk has the highest coefficient, indicating that the investors favour a conducive financial environment in deriving JII. Originality/value: This study extends the previous literature with an attempt to empirically examine the influence of Indonesia's country risk on the Islamic stock market through VECM.